2004
DOI: 10.1245/aso.2004.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Importance of Tumor Mitotic Rate Confirmed in 1317 Patients With Primary Cutaneous Melanoma and Long Follow-Up

Abstract: TMR was confirmed to be an important independent predictor of survival of patients with primary cutaneous melanoma. However, its predictive value was less than it was when assessed according to the 1982 revisions of the 1972 TMR recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
3
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 26 publications
6
109
3
7
Order By: Relevance
“…2 Unfortunately, we had no data regarding the mitotic rate of primary tumor, which was recently shown to be an independent prognostic variable in CM patients. 34 In addition, the sentinel lymph node status of our patients diagnosed during the early years of the study was not available, and for this reason we included all patients without clinical evidence of metastasis. Although SLNB significantly prolongs DFS, so far there is no evidence that this procedure has an impact on the DSS of patients with melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…2 Unfortunately, we had no data regarding the mitotic rate of primary tumor, which was recently shown to be an independent prognostic variable in CM patients. 34 In addition, the sentinel lymph node status of our patients diagnosed during the early years of the study was not available, and for this reason we included all patients without clinical evidence of metastasis. Although SLNB significantly prolongs DFS, so far there is no evidence that this procedure has an impact on the DSS of patients with melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…23 The mitotic rate (defined as mitoses/mm 2 ) of the primary tumor can serve as a measure for tumor proliferation and has been identified as an independent, adverse predictor of survival in patients with cutaneous melanoma. 24,25 The seventh edition of the American Joint Committee on Cancer (AJCC) staging system for melanoma now uses a mitotic rate of at least 1 mitosis/mm 2 as a primary criterion for defining stage T1b melanoma, replacing the former criterion of Clark level of invasion, because studies have demonstrated that an increasing mitotic rate is associated with declining survival rates, particularly within thin melanoma subgroups. 25,26 In the current study, we sought to determine whether or not there is a biologic difference in SPM and MPM to explain the observation that patients with MPM have thinner melanomas and a better prognosis than patients with SPM.…”
Section: Introductionmentioning
confidence: 99%
“…Barnhill et al compared the values of MR vs. ulceration in predicting the prognosis of localized melanoma; multivariate analysis of MR, ulceration, and tumor thickness showed that MR (<1, 1−6, and >6) is the most independent prognostic factor. In addition, some other studies also confirmed that MR is an important prognostic factor of skin melanoma (25)(26)(27)(28). According to the AJCC staging system (2010 edition), patients with an MR value of ≥1 is an independent prognostic factor of poor prognosis, in particular in patients with an infiltration thickness of ≤1 mm.…”
Section: Pathology Reportmentioning
confidence: 84%